Flexible Powder Production for Additive Manufacturing of Refractory Metal-Based Alloys - Frauke Hinrichs (MDPI AG, 2021)
The quality and properties of metal powders are essential for powder metallurgical (PM) processes in general and for additive manufacturing (AM) processing routes in particular. Thus, a variety of atomization technologies were established meeting the multiple needs of the different processing technologies. However, the production of refractory metal alloy powder remains challenging due to their high liquidus temperatures (>2000 °C), the formation of brittle intermetallic phases, as well as the reactivity with and sensitivity to interstitials of the constituting elements. In this contribution, powders made of Mo-20Si-52.8-Ti (at.%) were produced by a novel ultrasonic atomization (UA) process at laboratory-scale using an industrial electrode induction gas atomization (EIGA) process with a modified electrode concept for the first time. UA allows flexibility in alloy composition due to the arc melting-based principle, while the EIGA electrode is PM manufactured from elemental powders to provide similar flexibility on a larger scale. The powders resulting from these two processes were compared with respect to size distribution, sphericity, microstructure and phase constitution, chemical composition, and interstitial impurity content. In addition, several powder batches were produced with the UA process in order to assess the process reliability and stability. The properties, quality, and quantities of UA powders perfectly meet the requests for alloy development for powder bed fusion AM, while the modified EIGA process allows the upscaling of the alloy powder quantities.